Metanoia rhetoric, authenticity, and the transformation of the self - Ellwanger, Adam, 1978- (The Pennsylvania State University Press, 2020)
"Examines the concept of metanoia as both a rhetorical figure of speech and a critical tool for the analysis of self-reinventions of all kinds, including conversions related to race, sex, religion, and politics"--